Readapting to DCV Infection without Wolbachia: Frequency Changes of Drosophila Antiviral Alleles Can Replace Endosymbiont Protection. (27th June 2018) - Faria, Vitor G; Martins, Nelson E; Schlötterer, Christian; Sucena, Élio
Abstract: There is now ample evidence that endosymbionts can contribute to host adaptation to environmental challenges. However, how endosymbiont presence affects the adaptive trajectory and outcome of the host is yet largely unexplored. In Drosophila, Wolbachia confers protection to RNA virus infection, an effect that differs between Wolbachia strains and can be targeted by selection. Adaptation to RNA virus infections is mediated by both Wolbachia and the host, raising the question of whether adaptive genetic changes in the host vary with the presence/absence of the endosymbiont. Here, we address this question using a polymorphic D. melanogaster population previously adapted to DCV infection for 35 generations in the presence of Wolbachia, from which we removed the endosymbiont and followed survival over the subsequent 20 generations of infection. After an initial severe drop, survival frequencies upon DCV selection increased significantly, as seen before in the presence of Wolbachia . Whole-genome sequencing, revealed that the major genes involved in the first selection experiment, pastrel and Ubc-E2H, continued to be selected in Wolbachia -free D. melanogaster, with the frequencies of protective alleles being closer to fixation in the absence of Wolbachia . Our results suggest that heterogeneity in Wolbachia infection status may be sufficient to maintain polymorphisms even in the absence of costs.